Basics of biblical Greek grammar - Mounce, William D. (Zondervan language basics, 2019)
Basics of Biblical Greek Grammar is the standard textbook for beginning Greek language students in colleges and seminaries. It offers a clear, understandable, integrated approach to learning New Testament Greek. The fourth edition is updated throughout based on feedback from professors and students to make it even more useful